PUBLIC-PRIVATE PARTNERSHIP AS AN EFFECTIVE MECHANISM FOR SOCIAL INFRASTRUCTURE DEVELOPMENT - M. Arzumanyan (Вестник университета)
In this article the role of public-private partnership (PPP) in development of modern economy is investigated. The analysis of modern literature showed a variety of the points of view concerning distribution of resources and risks between partners and also the main criteria exerting impact on making decision on implementation of the project on the basis of PPP. In conclusion the author indicates the need of broader research of the factors promoting effective forming of relationship between the state and the private sector for improvement of life of citizens and increase in competitiveness of the country on the international scene.